2009
DOI: 10.3329/jsr.v1i2.2295
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Oxidative Stress Markers and Antioxidant Imbalance in HIV Infection and AIDS Patients

Abstract: The aim of this study was to investigate lipid peroxidation as evidenced by thiobarbutric acid reactive substances (TBARS), ceruloplasmin (Ce), CD 4+ cells counts and antioxidant, and micronutrients status in HIV infection and AIDS patients. The level of plasma and erythrocyte TBARS, plasma ceruloplasmin was markedly increased in the AIDS patients when compared to HIV infection and healthy control subjects. We observed a significant reduction in CD 4+ cell count in HIV/AIDS patients when compared to control su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 25 publications
2
18
1
Order By: Relevance
“…The present study revealed a decrease in the level of SOD in serum of HIV/ AIDS patients than control group but this decrease was statistically insignificant [27,28] . Such decrease may be due to its detoxification of released ROS (superoxide anion).…”
Section: Discussionmentioning
confidence: 81%
“…The present study revealed a decrease in the level of SOD in serum of HIV/ AIDS patients than control group but this decrease was statistically insignificant [27,28] . Such decrease may be due to its detoxification of released ROS (superoxide anion).…”
Section: Discussionmentioning
confidence: 81%
“…WHO (2011) reports showed that HIV infections evolved to acquired immune deficiency syndrome (AIDS) accompanied by opportunistic infections, severe metabolic and immune dysfunctions. Articles from Sonnerborg et al (1988), Stephens (2004), Pasupthi et al (2009), Coaccioli, et al (2010), Awodele et al (2012) and our group Gil et al (2003) have shown that humans infected with HIV are under chronic immune activation characterized by increase generation of ROS and perturbations of the antioxidant defence system. Oxidative stress (OS) has been detected in many tissues of HIV infected individuals using different biochemical's markers and diverse biotechniques.…”
Section: Introductionmentioning
confidence: 74%
“…Oxidative stress (OS) has been detected in many tissues of HIV infected individuals using different biochemical's markers and diverse biotechniques. In research studies by Sonnerborg et al (1988), Stephens (2004), Pasupthi et al (2009), Coaccioli, et al (2010), Awodele et al (2012), Redhage et al (2009), Stephensen, et al (2007) and Wanchu et al (2009) the OS characterization has been made in populations from several countries and different risk groups using case-controls, cross-sectional and interventions studies. These researches show imbalance in redox status during the infection course which could be related to oxidative molecular damage, viral replication, micronutrient deficiency and inflammatory chronic response, all of them implicated in cellular apoptosis and decreased immune proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…Since cellular redox status is a normal physiological variable, any imbalance may elicit cellular response through proliferation, transcriptional activation, or apoptosis [17]. For this reason, recent reports suggest that OS is a principal mechanism in the progression of AIDS [21][22][23].…”
Section: Hiv: An Oxidative Rolementioning
confidence: 99%
“…However, the discovery of HIV also led to a broadening of the view that ROS play a critical role in the expression of HIV and the development of AIDS [20]. It has been reported that the virus induces OS by disturbing cellular antioxidant defense and initiating oxidative reactions [21]. Advanced cases of HIV infection renders individuals susceptible to opportunistic infections, which take advantage of the progressive immunodeficiency caused by HIV.…”
Section: Hiv: An Oxidative Rolementioning
confidence: 99%